Exploring the key drivers behind the adoption of mobile banking services. Issue 3 (December 2017) - Nisar, Tahir; Prabhakar, Guru
Abstract This research examines the main drivers behind the adoption of mobile banking, a concept that has revolutionized the day-to-day activities of humans. A review of relevant literature on the topic, leads us toward testing the following key hypotheses: consumers are adopting mobile banking due to the perceived usefulness and benefits associated with the concept; and consumers are adopting mobile banking due to technological advances meaning increased access to the mobile phone devices. We published an online questionnaire on Amazon Mechanical Turk to obtain responses from Internet users. A dominating proportion of participants highlighted how mobile banking is a concept that they adopted between three and 5 years ago, showing just how recently mobile banking took off. The results also showed a number of links between the study's research hypotheses and the adoption of mobile banking. The overall result of the study shows online banking as a concept that is influenced by a number of both internal and external factors. No single factor plays a dominating force in pushing retail bankers to adopt mobile banking, with it instead being a culmination of numerous different factors. The recent introduction of mobile banking is made seemingly apparent, as is the increasing susceptibility to change in the near future. Subsequently, countless opportunities for further academic research are likely to arise.